2020
DOI: 10.9734/ejmp/2020/v31i1030289
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antimicrobial and Antioxidant Activities of Essential Oils of Four Species of the Lamiaceae Family

Abstract: Aims: The biological properties of essential oils represent possible therapeutic alternatives, with antimicrobial and antioxidant activities, and application in many areas of the industry. The objective was to determine the yield, chemical composition, antibacterial and antioxidant activities of the essential oils of Lavandula angustifolia, Pogostemon cablin, Rosmarinus officinalis, and Thymus vulgaris against Staphylococcus aureus, Salmonella enteritidis, Escherichia coli and Pseudomonas aeruginosa. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…The authors confirm that, as in our study, patchouli alcohol was the dominant component of the essential oil. Paulus et al [26] identified P. cablin paculol (31.5%), seichelene (13.6%), and α-bulnezene (15.6%) as the main components of the essential oil. The authors' results correlate with our findings even though they detected a higher proportion of seichelene than in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors confirm that, as in our study, patchouli alcohol was the dominant component of the essential oil. Paulus et al [26] identified P. cablin paculol (31.5%), seichelene (13.6%), and α-bulnezene (15.6%) as the main components of the essential oil. The authors' results correlate with our findings even though they detected a higher proportion of seichelene than in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Soh et al [30] determined the IC 50 at various extractions from 0.42 to 1.92 mg/mL and evaluated this activity as excellent. Paulus et al [26] determined the antioxidant activity of P. cablin at 12.08 µmol Trolox/mL. Mansuri et al [31] detected PCEO free radical scavenging activity with an IC 50 of 19.53 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature survey revealed that P. cablin essential oils showed antimicrobial activity (Das et al ., 2013; Kocevski et al ., 2013; Paulus et al ., 2020). Agusnar et al ., (2018) reported that chitosan films that added patchouli oil showed increased antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of PCEO‐CN was determined by measuring free radical scavenging potencies using 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) (Paulus et al ., 2020) (Materials and methodology S5). Antioxidant activityfalse(%false)=(BT)B×100,…”
Section: Materials and Methodologymentioning
confidence: 99%